1/n(n + 1) = (n + 1 - n)/n(n + 1) = 1/n - 1/(n + 1)
1/1*2 = 1 - 1/2
1/2*3 = 1/2 - 1/3
1/(1*2)+1/(2*3) + 1/(3*4)+...+1/(1017* 1018) = 1 - 1/2 + 1/2 - 1/3 + 1/3 - 1/4 + ... + 1/1017 - 1/1018 = 1 - 1/1018
1-1/1018
Пошаговое объяснение:
каждую дробь представим в виде разности: 1/1×2=1-1/2;
1/2×3=1/2-1/3;
1/3×4=1/3-1/4
..........
1/1017×1018=1/1017-1/1018. тогда имеем:
что и требовалось доказать
1/n(n + 1) = (n + 1 - n)/n(n + 1) = 1/n - 1/(n + 1)
1/1*2 = 1 - 1/2
1/2*3 = 1/2 - 1/3
1/(1*2)+1/(2*3) + 1/(3*4)+...+1/(1017* 1018) = 1 - 1/2 + 1/2 - 1/3 + 1/3 - 1/4 + ... + 1/1017 - 1/1018 = 1 - 1/1018
1-1/1018
Пошаговое объяснение:
каждую дробь представим в виде разности: 1/1×2=1-1/2;
1/2×3=1/2-1/3;
1/3×4=1/3-1/4
..........
1/1017×1018=1/1017-1/1018. тогда имеем:
что и требовалось доказать